Essential themes in Personnel economics - Dushko Josheski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper are presented essential themes in the subject of personnel economics. In the first part analysis has been conducted on the impact of peer pressure on workplace behaviour. Then again models for compensation structures within firms, and their influence on the utility of work by employees. In the final section of the paper the productivity spillover effect has been analyzed, and the causes of existence of spillovers and their impact on workers' productivity
Keywords: M00; M52; M55; 330; Personnel economics; compensation structures; peer pressure; spillover effect